Arte y Verdad. El pensamiento de J.D. García Bacca - Sevilla, Sergio (Bollettino Filosofico, 2017)
The split between the spheres of truth and beauty, that is stressed by modernity, has led present-day thought to rethink the meaning of truth, in connection with art, so as not to leave truth reduced to scientistic verificationism. The paper specifies the meaning of both spheres in the work of J.D. García-Bacca, a philosopher of the twentieth century who proposed to understand truth as an active creation that abandons the correspondence theory of truth, typical of epistemological representationalism.